Getting grounded? Miners' migration, housing and urban settlement in Tanzania, 1980–2012. Issue 3 (July 2019) - Jønsson, Jesper Bosse; Bryceson, Deborah Fahy; Kinabo, Crispin; Shand, Mike
Highlights: Migration to mining settlements is initially provisional. Staying, returning home or moving on to other mining sites relates to livelihood outcomes and life cycle needs in the context of deagrarianization. Housing gradually improves unless investment elsewhere or livelihood insecurity prevails. Residential stability of mining settlements is most pronounced in occupationally diversified locations. Mining settlement stimulates rapid urbanization. Abstract: In the 1960s, Mitchell applied situational analysis to the question of miners' residential stability on the Zambian Copperbelt. African mining has evolved since then and spread continentally. During the 1990s, artisanal mineral sites proliferated in northwest Tanzania, absorbing an increasingly significant segment of the national population in urbanizing settlements amidst deagrarianization. Thereafter foreign investment and the operational establishment of a number of large-scale mine sites attracted further in-migration. This article interrogates the residential stability of three types of mining settlements: artisanal rush sites, mature artisanal site and large-scale mining sites. Mining settlement residents' migration histories, occupational pursuits, housing, investments, concepts of home and anticipated places of retirement, are probed to explore the question of just how grounded migrants are in mining settlements, the extent they identify as urbanites and how their residential and occupational patterns contrast with preceding mid-twentieth century miners' migration in Southern Africa.